PENDEKATAN KETERAMPILAN PROSES TERHADAP KETERAMPILAN MENULIS SISWA KELAS V SD NEGERI 17 PONTIANAK UTARA - Amalia, Winda; Halidjah, Siti; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The purpose of this study to characterize how the process skills method has affected the writing abilities of State Elementary School 17 North Pontianak grade V students. A quasi-experimental design with a nonequivalent control group design was the methodology chosen for this study. The population consisted of 27 pupils from class V A and 27 students from class V C. Since all individuals of the population were employed as samples, the sampling strategy used in this study was nonprobability sampling with saturation sampling type. A written test in the form of an essay or description serves as both the data collection tool and the measurement approach. According to the data analysis, the mean score of the experimental class on the post-test was 69.09, while the mean score of the control class was 53.926. Applying the process skills approach to students"™ writing skills was effective, as shown by the results of hypothesis testing using t-tests. This resulted in tcount = 9.01 and ttable = 2.06 for dk = 52, with a significance level of Î± = 5%. This indicates that Ha is accepted. According to the effect size (ES) calculation results, ES = 0.38, which meets the moderate standards. Therefore, it can be said that the use of the process skills method improves the writing abilities of State Elementary School 17 North Pontianak grade V students.